Removal of a model reactive azo dye from aqueous solution by a bioadsorbent in batch and fixed-bed column modes: Application of the developed technology to a textile wastewater - Natália Roberta Marques Tanure; Luisa Cardoso Maia; Liliane Catone Soares; Megg Madonyk Cota Elias; Grazielle Pereira da Silva; Eduardo Ribeiro de Azevedo; Leandro Vinícius Alves Gurgel (Water Resources and Industry)
Sugarcane bagasse (SB) was used to produce a new bioadsorbent (STEA), drawing on circular economy concepts. STEA was synthesized using a two-step one-pot reaction, employing epichlorohydrin and triethylamine in the presence of N,N-dimethylformamide, without the use of a petroleum-based catalyst. The structure and surface of STEA were characterized by elemental C, H, N, and Cl analysis, X-ray diffraction, infrared spectroscopy, 13C solid-state nuclear magnetic resonance spectroscopy, thermogravimetric analysis, specific surface area and pore size distribution determination, and point of zero charge measurement. Batch adsorption and desorption tests were performed with the model dye Remazol Golden Yellow (RGY) RNL, a reactive anionic azo dye widely used in textile industry, to evaluate the potential reuse and application of STEA in a fixed-bed column for wastewater treatment. For batch adsorption, the best dose and agitation speed were 0.2 g L−1 and 50 rpm, respectively. STEA effectively removed RGY over a wide range of pH (2.00–10.00). The equilibrium time, maximum adsorption capacity (Qmax), and desorption efficiency (Edes) were 720 min, 369 mg g−1 (0.71 mmol g−1), and 49.5 %, respectively. The fixed-bed column fed with a spiked aqueous RGY solution could be operated for 415 min, with Qmax of 422 mg g−1 (0.81 mmol g−1) and Edes of 58.9 %. Batch and continuous experiments using real textile industry wastewater containing reactive azo dyes showed high color removal efficiency by STEA, with no interference of other compounds present in wastewater on adsorption of the reactive azo dyes (overshooting effect). The technology was validated in a relevant environment and achieved technology readiness level 5, showing potential to be upscaled. Therefore, STEA proved to be an efficient bio-based technology for application in tertiary treatment of real textile plant wastewater to remove reactive anionic azo dyes.